Acute beetroot juice consumption does not alter cerebral autoregulation or cardiovagal baroreflex sensitivity during lower-body negative pressure in healthy adults - Worley, Morgan L.; Reed, Emma L.; Chapman, Christopher L.; Kueck, Paul; Seymour, Lauren; Fitts, Triniti; Zazulak, Hannah; Schlader, Zachary J.; Johnson, Blair D. (Frontiers in Human Neuroscience, 2023)
Beetroot juice (BRJ) improves peripheral endothelial function and vascular compliance, likely due to increased nitric oxide bioavailability. It is unknown if BRJ alters cerebrovascular function and cardiovagal baroreflex control in healthy individuals. Purpose: We tested the hypotheses that BRJ consumption improves cerebral autoregulation (CA) and cardiovagal baroreflex sensitivity (cBRS) during lower-body negative pressure (LBNP). Methods: Thirteen healthy adults (age: 26±4 y; 5 women) performed oscillatory (O-LBNP) and static LBNP (S-LBNP) before (PRE) and 3 hours after consuming 500 mL of BRJ (POST). Participants inhaled 3% CO2 (21% O2, 76% N2) during a 5 minute baseline and throughout LBNP to attenuate reductions in end-tidal CO2 tension (PETCO2). O-LBNP was conducted at ~0.02 Hz for six cycles (-70 mmHg), followed by a 3-min recovery before S-LBNP (-40 mmHg) for seven minutes. Beat-to-beat middle cerebral artery blood velocity (transcranial Doppler) and blood pressure were continuously recorded. CA was assessed using transfer function analysis to calculate coherence, gain, and phase in the very-low-frequency (VLF; 0.020-0.070 Hz) and low-frequency bands (LF; 0.07-0.20 Hz). cBRS was calculated using the sequence method. Comparisons between POST vs. PRE are reported as mean ± SD. Results: During O-LBNP, coherenceVLF was greater at POST (0.55±0.06 vs. 0.46±0.08; P<0.01), but phaseVLF (P=0.17) and gainVLF (P=0.69) were not different. CoherenceLF and phaseLF were not different, but gainLF was lower at POST (1.03±0.20 vs. 1.12±0.30 cm/s/mmHg; P=0.05). During S-LBNP, CA was not different in the VLF or LF bands (all P>0.10). Up-cBRS and Down-cBRS were not different during both LBNP protocols. Conclusion: These preliminary data indicate that cerebral autoregulation and cardiovagal baroreflex sensitivity during LBNP in healthy, young adults is largely unaffected by an acute bolus of BRJ.